Use of E-Learning Model and Social Media in Social Studies Learning in Elemenrary School During and After the Covid-19 Pandemic - Azlansyah Armansyah; Erni Munastiwi (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to provide information related to the use of e-learning model and social media that are utilized to develop image of social studies learning in elementary school in the pandemic era and after the Covid-19 pandemic. The type of research used was library research, with the following results: (1) Elementary social studies learning is expected to provide insightful concepts to students and teachers to use e-learning and social media during and after the Covid-19 pandemic, such as : web courses, web-centric courses, and web-enhanced courses, therefore the attitudes and perceptions of students and teachers social studies learning in elementary school need to be improved for creating meaningful social studies learning, (2) As a supporting aspect in elementary school social studies subject because this method is more effective during and after the Covid-19 pandemic, (3) Able to apply e-learning and social media in social studies learning to improve the quality of education and adapt to the current era.